2024
DOI: 10.1002/jev2.12460
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of urinary podocyte‐derived migrasomes for the diagnosis of kidney disease

Rong Yang,
Heng Zhang,
Si Chen
et al.

Abstract: Migrasomes represent a recently uncovered category of extracellular microvesicles, spanning a diameter range of 500 to 3000 nm. They are emitted by migrating cells and harbour a diverse array of RNAs and proteins. Migrasomes can be readily identified in bodily fluids like serum and urine, rendering them a valuable non‐invasive source for disease diagnosis through liquid biopsy. In this investigation, we introduce a streamlined and effective approach for the capture and quantitative assessment of migrasomes, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…WGA is an example of such lectins ( 25 ). We previous introduced an innovative, user-friendly and highly efficient technique for the capture and quantitative analysis of EVs by leveraging WGA-coupled magnetic beads in conjunction with flow cytometry ( 19 ). In order to further simplify the operation process and cost, we developed a novel platform for uEVs capture and detection by WGA-coupled magnetic beads and CLIA ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WGA is an example of such lectins ( 25 ). We previous introduced an innovative, user-friendly and highly efficient technique for the capture and quantitative analysis of EVs by leveraging WGA-coupled magnetic beads in conjunction with flow cytometry ( 19 ). In order to further simplify the operation process and cost, we developed a novel platform for uEVs capture and detection by WGA-coupled magnetic beads and CLIA ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified differentially expressed proteins and RNAs in the uEVs of breast cancer patients ( 14 18 ). In our previous study, we introduced an innovative, user-friendly and highly efficient technique for the capture and quantitative analysis of EVs by leveraging wheat germ agglutinin (WGA)-coupled magnetic beads in conjunction with flow cytometry ( 19 ).…”
Section: Introductionmentioning
confidence: 99%